2013
DOI: 10.1007/s00216-013-6872-7
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized purine nucleoside phosphorylase from Schistosoma mansoni for specific inhibition studies

Abstract: The parasite Schistosoma mansoni (Sm) depends exclusively on the salvage pathway for its purine requirements. The enzyme purine nucleoside phosphorylase (PNP) is, therefore, a promising target for development of antischistosomal agents and an assay for screening of inhibitors. To enable this, immobilized SmPNP reactors were produced. By quantification of hypoxanthine by liquid chromatography, kinetic constants (K M) for the substrate inosine were determined for the free and immobilized enzyme as 110 ± 6.90 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It was previously demonstrated that the immobilization of proteins provides in some cases increased stability [3638], due to the more restricted conformational mobility. A similar increase in stability was observed with the immobilization of PrP C , preventing the conversion of PrP C to PrP Sc and PrP Sc -like isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously demonstrated that the immobilization of proteins provides in some cases increased stability [3638], due to the more restricted conformational mobility. A similar increase in stability was observed with the immobilization of PrP C , preventing the conversion of PrP C to PrP Sc and PrP Sc -like isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…The S. mansoni purine nucleoside phosphorylase (SmPNP) activity and structure have been well characterized [124][125][126]. Selective inhibitors for SmPNP have been tested in enzymatic assays in vitro; however, experiments with parasite larval or adult stages have not been reported yet [127][128][129]. The hypoxanthine-guanine phosphoribosyltransferase (HGPRTase) was also considered as a potential drug target [130].…”
Section: Purine Biosynthesismentioning
confidence: 99%
“…Zonal bioaffinity chromatography has previously been successfully used for ICERs characterization through Michaelis-Menten parameters by means of a 2D LC system. 1,2 Herein, an XO-ICER was prepared and used in the first dimension of a 2D LC system (Figure 3) to not only determine its kinetic parameters but also fully characterize its tight-binding inhibitors. The validated LC method was used to quantify the production of uric acid by the ICERs.…”
Section: Xo-icer Preparation and Kinetics Parametersmentioning
confidence: 99%